La funzione affettivo-educativa dei genitori nell’affidamento “diviso”. Una nota di commento pedagogico al disegno di legge Pillon - Taraschi, Monja (Rivista Italiana di Educazione Familiare, 2019)
The paper deals with the issue of the parents’ affective-educational function towards their offspring, after the failure of their union and comments on the Pillon bill. This bill strictly defines the time spent by minor children with each of the parents. This option appears very critical: the task of the legislator should only be to define a principle; the time for children to attend with each parent should be ample, bearing in mind the concrete situation and children’s need for a serene and balanced growth. The Pillon bill also offers the opportunity for an educational reflection on the topic of the “right of love”, as a subjective right to parental affection, essential for the emotional life of children and for their harmonious education. Denying the right of love means denying freedom and dignity.